THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE PERSONALISATION OF DIGITAL LEARNING: A SYSTEMATIC REVIEW OF CURRICULUM ADAPTATION AND PUPILS’ ACADEMIC ACHIEVEMENT - Zayid Musiafa; Parni (Indonesian Journal of Education (INJOE), 2026)
This study aims to examine the role of artificial intelligence in the personalisation of digital learning through a systematic review of curriculum adaptation and pupils’ academic achievement. Artificial intelligence is increasingly being applied in education due to its ability to analyse pupils’ learning data in real time, adapt learning materials, and provide relevant feedback tailored to individual needs. Through a personalised approach, AI enables the learning process to become more adaptive, flexible and learner-centred. The findings indicate that AI contributes to supporting curriculum adaptation by tailoring content, the pace of learning and learning strategies to better suit learners’ characteristics. Furthermore, AI also has a positive impact on pupils’ academic achievement by enhancing their understanding of the subject matter, their motivation to learn and their engagement in the learning process. Nevertheless, the implementation of AI in education still faces challenges such as data privacy, infrastructure readiness, teacher competence, and the digital divide. Therefore, the integration of AI into digital learning must be carried out wisely, ethically, and sustainably in order to provide optimal benefits for improving the quality of education.